Seven Pillars of Business Ethics: Toward a Comprehensive Framework - Wines, William Arthur (Journal of business ethics, 2008)
This article first addresses the question of “why” we teach business ethics. Our answer to “why” provides both a response to those who oppose business ethics courses and a direction for course content. We believe a solid, comprehensive course in business ethics should address not only moral philosophy, ethical dilemmas, and corporate social responsibility – the traditional pillars of the disciple – but also additional areas necessary to make sense of the goings-on in the business world and in the news. These “new pillars,” that we advocate include moral psychology, organizational design and behavior, motivational theory, and a unit on how society, business, and law interact. This last unit builds upon the work of Francis P. McHugh (1988) who urged an integration of “disciplines related to business ethics.” Our seventh pillar would encompass an integration of law, socio-political theory, and policy to demonstrate how business helps construct its own regulatory framework. The concluding recommendation is for a comprehensive “Seven Pillars” of business ethics approach.